Bridging Gaps and Building Futures: Navigating Challenges and Harnessing Opportunities for Children’s Library Services in Eastern Uganda - Nalumansi, Mary; Kaddu, Sarah B.; Okello- Obura, Constant (Global Journal of Arts Humanity and Social Sciences, 2024)
Purpose: This research explored the prospects and difficulties in practicing literacy with children at the Nambi Sseppuuya Community Resource Centre in Jinja District – Uganda. Methods: The study incorporated a qualitative research concept. Interviews were conducted with some of the selected parents and with the librarians, and focus group discussions whereby 80 children aged between 6 and 13 years. Findings: The study established that there are multiple programs for children in the library including; training reading sessions, story-telling and formation of reading clubs. At the same time, a number of problems were revealed, such as insufficient financing, the lack of staff, the problem of security, and poverty affecting children‟s books‟ availability. The study also noted that reading is mostly initiated by parents when the child joins formal school making it hard for their early reading. Furthermore, because the education system puts much emphasis on examination performance, children are discouraged from reading for recreation. In the course of the research, the following possibilities were found useful for enhancing children‟s reading: Some teaching strategies which could help facilitate literacy are establishing a print-rich environment, offering multiple text choices, modeling appropriate readers, maintaining interest in reading, reading to children, sharing a good relation with teachers, promoting choral reading and last but not least, should encourage children. Practical implications: We need to learn strategies for addressing issues public libraries experience while effectively managing existing opportunities for promoting reading culture among children. Community libraries can benefit children‟s future literacy by funding reading programmes.